#TITLE_ALTERNATIVE# - Endreswari (NIM : 20793003), Sri
Abstract: The study of the influence of cimetidine on the anti-inflamatory activity of diclofenac using edema inhibitory method in rats and its pharmacokinetic parameters in rabbits has been carried out using random cross over design. For the anti-inflamatory activity test, sodium diclofenac was administered orally at a doses of 1.23 ; 1.85 and 2.78 mg/100 g body weight to a group of rats receiving a single dose of cimetidine of 4.5 mg/100 g body weight, a group of rats receiving multiple dose of cimetidine of 4.5 mg/100 g body weight per day for seven days, and a group of rats without cimetidine. The result showed that the inhibition effect of sodium diclofenac at a dose of 1.23 mg/100 g body weight one hour after administration of sodium diclofenac from the cimetidine single dose group and a dose of 1.85 mg/100 g body weight three hours after adminstration of sodium diclofenac from the cimetidine multiple dose group were significantly different (oc=0.05) compared to the control. For the pharmacokinetic study, sodium diclofenac was administered intravenously at a dose of 14.46 mg/kg body weight to rabbits 30 minutes after administration of cimetidine at a dose of 23.40 mg/kg body weight and to rabbits receiving a saline solution as control. The result showed that the elimination half-life and the area under the curve were increased while the total body clearance and the distribution volume were decreased,compared to the control (specially for the area the under curve and the distribution volume showed a big different), but statistically were not significantly different.